+0  
 
+1
4
1
avatar+218 

Let \(a_1, a_2, a_3,\dots\) be a sequence. If \(a_n = a_{n - 1} + a_{n - 2}\)for all \(n \ge 3,\) and \(a_{11} - a_1 = 4,\) then find \(a_6.\)

 Apr 29, 2024
 #1
avatar+128772 
+1

a11 - a1  =   4

 

a10 + a9  = 4 + a1

 

(a8 + a9) + a9  = 4 + (a3 - a2)

 

2a9 + a8  = 4 + a3 - a2

 

2(a8 + a7) + a8  = 4 + ( a5 -a4) - ( a4 - a3)

 

3a8 + 2a7  =   4 + a5 - 2a4 + a3

 

3 ( a7 + a6) + 2a7  = 4 + (a7 -a6) - 2(a6 -a5) + (a5 - a4)

 

5a7 + 3a6 =  4 + a7 - 3a6 + 3a5 - a4

 

4a7 + 6a6 = 4 + 3a5 - a4

 

4a7 + 6a6  = 4 + 3(a7 -a6) - (a6 -a5)

 

4a7 + 6a6  = 4 + 3a7 - 4a6 + a5

 

a7 +10a6 = 4 + a5

 

(a6 + a5) + 10a6 = 4 + a5

 

a6 + a5  + 10a6 = 4 + a5

 

11a6  = 4

 

a6 =  4 /  11

 

cool cool cool

 Apr 29, 2024

6 Online Users

avatar
avatar
avatar
avatar
avatar
avatar